Leucanthemum vulgare lam. crude oil phytoremediation. Issue 13 (10th November 2018) - Noori, Azam; Zare Maivan, Hassan; Alaie, Ebrahim; Newman, Lee A.
Abstract: Sites with crude oil pollution have been successfully treated using phytoremediation, but expanding the range of plants that can be used and understanding how exposure impacts the plants are two areas of study that are important to continue. Leucanthemum vulgare has been shown to grow well under a variety of stressful conditions. To examine L. vulgare 's ability to both survive crude oil exposure and to reduce crude oil concentrations in soil, plants were placed in soil containing 0, 2.5, 5, 7.5, or 10% w/w crude oil. Total petroleum hydrocarbons (TPH) concentration, peroxidase and catalase activity, proline and phenol content in roots and leaves were determined at the start of planting and every 2 months for 6 months. L. vulgare roots were successfully colonized with mycorrhizae under all conditions. Results showed positive correlation between antioxidant compound concentration and crude oil contamination. Also, a significant reduction occurred in TPH content of soil over time in planted pots as compared to controls. The lowest TPH content was recorded after 6 months under all treatments. Results showed L. vulgare could survive crude oil exposure and enhance reducing of crude oil from soil.